Alcohol Use and Cancers of the Gastrointestinal Tract. Epidemiology and Preventive Implications - Rehm, Jürgen; Shield, Kevin (Frontiers in Oncology, 2020)
Introduction: Alcohol is a carcinogen for human cancer. This contribution summarizes the relationships between alcohol use and gastrointestinal cancers, and implications for prevention. Methods: Comparative risk assessment and narrative literature review Results: The following gastrointestinal cancer sites were found to be causally impacted by alcohol use: lip and oral cavity, pharynx other than nasopharynx, esophagus, colon and rectum, and liver. Globally, 368,000 deaths (304,000 men and 64,000 women) and more than 10 million disability-adjusted life years (DALYs) lost (10.1 million; 8.4 million men and 1.6 million women) in 2016 were attributable to alcohol use, making up about 10% of all deaths and DALYs lost due to these cancers, respectively. There are effective and cost-effective alcohol control policies available to reduce this burden, namely the best buys of increasing taxation, reducing availability, and banning advertisement. In addition, public knowledge about the alcohol-cancer link should be increased. Discussion: There are a number of assumptions underlying these estimates, but overall all of them seem to be conservative.